A Romanian 19th century document from the Vidin region - Sorescu-Marinković, Annemarie (Swedish Journal of Romanian Studies, 2021)
By bringing to the readers’ attention an unpublished Ottoman era document in Romanian, issued in 1861 in Rabrovo, a village in the Vidin region, back then under Ottoman rule, the article tries to shed light on the wider historical and sociolinguistic context of the Romanian-speaking population south of the Danube in the 19th century. The document is a donation-adoption act by which a Romanian man gives one of his sons for adoption to his brother, who does not have heirs. The document is handwritten in Romanian, using Cyrillic script, signed by the chorbaji, mayor and eight witnesses, and stamped by the Turkish administrator. Though very short, it reveals several important facts about the Romanian-speaking population in Ottoman Bulgaria and its origin, the language used in communication and writing, family relations, etc. Coming from a family archive, this document of great emotional value for its owner, has also undisputable linguistic and historical significance.